Efficiency Enhancement of Carbon Nitride Photoelectrochemical Cells via Tailored Monomers Design. Issue 12 (5th April 2016) - Bian, Juncao; Xi, Lifei; Huang, Chao; Lange, Kathrin M.; Zhang, Rui‐Qin; Shalom, Menny
Abstract : Uniform carbon nitride electrodes, with enhanced photoelectrochemical cell (PEC) performance, are successfully developed by clever design of monomers interaction at high temperatures using thermal vapor condensation method. The monomers alteration leads to a significant improvement of the optical, electronic, and PEC properties of the carbon nitride films, resulting in incident photon‐to‐current efficiency of 16% at 400 nm.